EXPLORING FACTORS HINDERING MSME GROWTH IN SEYCHELLES: CHALLENGES AND STRATEGIES THE MSMES USE TO SUSTAIN BUSINESS - Barra, Julie Theresa; Singh , Jugindar Singh Kartar; Alwie , Sueraya Mohamad; Hussain , Ibiwani Alisa (Electronic Journal of Business and Management, 2022)
In Seychelles, MSMEs are regarded as the backbone of the economy. Despite their importance, there is a lack of in-depth studies on the specific challenges and survival strategies they employ. This research aims to explore the impediments to MSME growth and discover the strategies used to sustain business during a crisis. In this exploratory study, semi-structured interviews were conducted with owners of seven MSMEs in Seychelles. The findings revealed that most challenges were external, including financial constraints, lack of government support, supply chain disruption, drop in revenue, and labor availability. Key strategies for survival included promotion through social media, diversification, and other intensive strategies.